2022
DOI: 10.1111/jre.13022
|View full text |Cite
|
Sign up to set email alerts
|

LiCl‐induced immunomodulatory periodontal regeneration via the activation of the Wnt/β‐catenin signaling pathway

Abstract: BackgroundGrowing evidence suggests that excessive inflammation hampers the regenerative capacity of periodontal ligament cells (PDLCs) and that activation of the Wnt/β‐catenin pathway is crucial in suppressing immune dysregulation.ObjectiveThis study aimed to establish the role of the Wnt/β‐catenin in regulating the immune microenvironment and its subsequent impact on periodontal regeneration.MethodsLithium chloride (LiCl, Wnt activator) was administered daily into the standard periodontal defects created in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…While M2 macrophages produce a proregenerative milieu ideal for periodontal tissue repair and regeneration, inflammatory M1 macrophages inhibit PDLC differentiation and mineralization by secreting a range of proinflammatory cytokines 46,47 . BMP‐2, a member of the transforming growth factor‐β (TGF‐β) super family, is required in initiating the activation of Wnt signaling pathway that promotes the differentiation of PDLCs 4,48–50 . PAM treatment increased BMP‐2 production in M1 macrophage‐derived conditioned medium (Figure 5C,D), suggesting that PAM has the potential to be used in periodontal therapy as an enhancer for osteogenesis and cementogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While M2 macrophages produce a proregenerative milieu ideal for periodontal tissue repair and regeneration, inflammatory M1 macrophages inhibit PDLC differentiation and mineralization by secreting a range of proinflammatory cytokines 46,47 . BMP‐2, a member of the transforming growth factor‐β (TGF‐β) super family, is required in initiating the activation of Wnt signaling pathway that promotes the differentiation of PDLCs 4,48–50 . PAM treatment increased BMP‐2 production in M1 macrophage‐derived conditioned medium (Figure 5C,D), suggesting that PAM has the potential to be used in periodontal therapy as an enhancer for osteogenesis and cementogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The PDLCs used in this study were harvested from caries‐free and periodontally healthy premolars extracted for orthodontic treatment purposes ( n = 6). The periodontal ligament tissues were isolated from the mid‐third of the tooth root surfaces, trimmed to fine pieces, and rinsed with PBS 4 . The tissue explants were transferred to a T75 flask with DMEM containing 10% FBS and 1% P/S.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we can see some possible common mechanisms in other examples of inflammatory diseases. Through the study of periodontal regeneration, it has been shown that Wnt/β-catenin signaling activation can activate macrophage autophagy to promote the transformation to M2 type macrophages and achieve tissue repair [ 120 ]. Negative regulation of Wnt signaling by autophagy promotes the differentiation of Bone-marrow-derived macrophage (BMDM) into osteoclasts, thereby affecting tissue regeneration [ 121 ].…”
Section: Reviewmentioning
confidence: 99%